Oxotitanium(IV) Complexes with Dizao Compounds - Pujar, M.A.; Siddappa, K. (Asian Journal of Chemistry, 2010)
Oxotitanium (IV) complexes have been prepared by treating oxotitanium (IV) perchlorate with diazocompounds. The complexes are characterized by elemental analyses, molecular weight, infrared and electronic spectral studies. The results suggest that the complexes are five coordinated and have bipyramidal geometry.